When Courage Came to Call - Fuge, L. M.; Photography by SuperStock (North Sydney Random House Australia, 2010)
Everything changed when the first bomb fell. Now there is the Resistance. Now there are the rules. RULE ONE. We do our work under the cover of darkness. RULE TWO. If you trust me, I will trust you. RULE THREE. We work for the good and safety of Zamascus. This will include killing. Imm is about to find out if he has what it takes to survive - and what it will cost him.
Keywords: Youth and war -- War stories